(untitled) - Bryant, Stephen D. (U.S.A., 2019)
The Upper Room daily devotional guide provides a practical way to listen to scripture, connect with believers around the world, and spend time with God each day. You can spend time with God and receive encouragement for your faith journey through meditations that have been written by readers from all around the world. Each devotion includes a suggested Bible passage, a personal story relating the message of the scripture to daily life, a thought for the day, a prayer, and a prayer focus. Strengthen your faith and deepen your relationship with God through this devotional magazine.
Keywords: Spiritual life -- Christianity